1998
DOI: 10.1002/(sici)1097-0177(199806)212:2<167::aid-aja1>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene trapping—a preface

Abstract: Fig. 1. The average number of unique clones found per 1,000 picked for a variety of total genome target sizes and for between 0% and 20% of the loci being hit at 1-20 times normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, as has been found in homologous-recombination experiments, there are 'hot' and 'cold' genomic spots for gene-trap vector insertions. But, computer modelling, albeit with a limited data set, has indicated that on the basis of the percentage of unique clones that have been trapped, and given enough rounds of mutagenesis and enough different types of vector to negate biases, virtually the entire ES-cell genome could be saturated with insertions 36 . This modelling exercise needs to be repeated using the new data sets from the large genotype-driven screens; however, data from the German Gene Trap Consortium, which has used four different vectors to isolate ~6,000 sequences that represent ~4,500 genes (BOX 2) (W. Wurst, personal communication), are consistent with this model.…”
Section: New Vector Designsmentioning
confidence: 99%
“…However, as has been found in homologous-recombination experiments, there are 'hot' and 'cold' genomic spots for gene-trap vector insertions. But, computer modelling, albeit with a limited data set, has indicated that on the basis of the percentage of unique clones that have been trapped, and given enough rounds of mutagenesis and enough different types of vector to negate biases, virtually the entire ES-cell genome could be saturated with insertions 36 . This modelling exercise needs to be repeated using the new data sets from the large genotype-driven screens; however, data from the German Gene Trap Consortium, which has used four different vectors to isolate ~6,000 sequences that represent ~4,500 genes (BOX 2) (W. Wurst, personal communication), are consistent with this model.…”
Section: New Vector Designsmentioning
confidence: 99%
“…In this context, gene trapping in embryonic stem (ES) cells provides a tagged insertional mutagenesis suited for large‐scale studies (reviewed by Zambrowicz and Friedrich, 1998). Gene trapping by random insertional mutagenesis tags genes in ways that allows facile determination of their expression pattern and DNA sequence, as well as the generation of mouse mutants (Gossler et al, 1989; reviewed by Evans et al, 1997; Evans, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Gene trapping, on the other hand, is a form of random insertional mutagenesis specifically designed to disrupt and retrieve genes in target cells by producing intragenic vector integration events (4,5). Hundreds or even thousands of genome sequences in mouse ES cells can be ''trapped'' in a relatively short period (6,7).…”
mentioning
confidence: 99%